Possible causes and treatment strategies for the estrus and ovulation disorders in dairy cows - Natsumi ENDO (The Society for Reproduction and Development, 2022)
The reproductive performance of dairy cows has declined, along with an increase in their milk yield. First-service conception rates in lactating dairy cows are often lower than 50%. The precise detection of estrus is an important factor in the reproductive management of dairy cows for successful fertilization and pregnancy. However, estrus expression has been decreasing in modern dairy cows, affecting the detection rate of estrus. In addition to estrus, a high incidence of ovulation disorders affects the fertility of dairy cows. To address these problems, it is necessary to understand the changes in the endocrine functions that underlie estrus and ovulation disorders, and to develop effective treatment strategies. Recent studies have revealed that neurokinin B and neurokinin 3 receptor signaling play important roles in the regulation of the secretion of gonadotropin-releasing and luteinizing hormones, suggesting a potential clinical avenue for the stimulation of gonadal function. In this review, I have discussed the problems in estrus and ovulation disorders in modern dairy cows as well as the possible applications of neurokinin 3 receptor agonists in the treatment of these disorders.